Comparative analysis on the fertiliser responses of Martonvásár maize hybrids in long-term experiments - Takács, Nóra; Micskei, Györgyi; Berzsenyi, Zoltán (Acta Agraria Debreceniensis, 2008)
The results of experiments carried out in the Agricultural Research Institute of the Hungarian Academy of Sciences clearly show that in the case of hybrids grown in a monoculture greater fertiliser responses can be achieved with increasing rates of N fertiliser than in crop rotations. In the monoculture experiment the parameters investigated reached their maximum values at a rate of 240 kg/ha N fertiliser, with the exception of 1000-kernel mass and starch content. In both cases the starch content was highest in the untreated control, gradually declining as the N rates increased. Among the parameters recorded in the crop rotation, the values of the dry grain yield, the 1000-kernel mass, the protein yield and the starch yield were greatest at the 160 kg/ha N fertiliser rate, exhibiting a decrease at 240 kg/ha. Maximum values for the protein content and SPAD index were recorded at the highest N rate. It is important to note, however, that although the N treatments caused significant differences compared to the untreated control, the differences between the N treatments were not significant. In the given experimental year the values achieved for the untreated control in the crop rotation could only be achieved in the monoculture experiment at a fertiliser rate of 160 kg/ha N, indicating that N fertiliser rates could be reduced using a satisfactory crop sequence, which could be beneficial from the point of view of environmental pollution, crop protection and cost reduction. The weather in 2006 was favourable for maize production, allowing comparative analysis to be made of the genetically determined traits of the hybrids. Among the three hybrids grown in the monoculture experiment, Maraton produced the best yield, giving maximum values of the parameters tested at a fertiliser rate of 240 kg/ha N. The poorest results were recorded for Mv 277, which could be attributed to the fact that the hybrid belongs to the FAO 200 maturity group, while the other hybrids had higher FAO numbers. Maraton also gave the highest yields in the crop rotation experiment at the 160 kg/ha N level. All three hybrids were found to make excellent use of the natural nutrient content of the soil. It was proved that the protein content of maize hybrids can only be slightly improved by N fertilisation, as this trait is genetically coded, while the starch content depends to the greatest extent on the ecological factors experienced during the growing season.